Hydrogen sulfide treatment induces angiogenesis after cerebral ischemia. Issue 11 (17th June 2014) - Jang, Hyunduk; Oh, Mi‐Young; Kim, Young‐Ju; Choi, In‐Young; Yang, Hye sung; Ryu, Wi‐Sun; Lee, Seung‐Hoon; Yoon, Byung‐Woo
<x xml:space="preserve">Abstract</x> Hydrogen sulfide (H2S) is a potent vasodilator and regulates cardiovascular homeostasis. Furthermore, H2S has a crucial role in ischemia−reperfusion injuries, especially of the heart, liver, and kidneys. This study indicates that treatment with hydrogen sulfide is able to restore neurological function after ischemic stroke by promoting angiogenesis. Treatment with H2S augments angiogenesis in the peri‐infarct area, and it significantly improves functional outcomes after 2 weeks in a rat MCAO model. H2S promotes the phosphorylation of AKT and ERK and increases the expression of vascular endothelial growth factor (VEGF) and angiopoietin‐1 (Ang‐1). H2S‐treated rats showed more newly synthesized endothelial cells in the ischemic lesion (2.31‐fold, P < 0.01). H2S‐treated astrocytes increased VEGF and Ang‐1 expression, and the inhibition of phosphatidylinositide 3‐kinase (PI3K)/AKT signaling by LY294002 significantly reduced H2S‐induced VEGF and Ang‐1 expression in astrocytes. Finally, H2S stimulated endothelial cell migration (3.92‐fold increase in wound healing assay) and tube formation (3.69‐fold increase, P < 0.001) through PI3K/AKT signaling. In conclusion, treatment with H2S promotes angiogenesis and thereby contributes to improvement of functional outcome after cerebral ischemia. Our findings strongly suggest that H2S may be of value in regenerative recovery after stroke. © 2014 Wiley Periodicals, Inc.